Automated Intra-abdominal Pressure Monitoring During Orthotopic Heart Transplant Leads to Early Diagnosis and Treatment of Intraoperative Abdominal Compartment Syndrome—A Case Report - Zhao, Manxu; D'Attellis, Nicola; Emerson, Dominic; Moll, Vanessa; Esmailian, Fardad (Frontiers in Surgery, 2022)
We describe a case of spontaneous retroperitoneal hematoma leading to abdominal compartment syndrome and organ failure during a complicated orthotopic heart transplantation in a patient previously on mechanical circulatory support. After the patient had been weaned of cardiopulmonary bypass, the patient suddenly became hemodynamically unstable despite good LV and RV function. While the patient was resuscitated, high intra-abdominal pressures were noted on a novel monitor measuring real-time intra-abdominal pressures and urinary output. The early detection of high intra-abdominal pressures led to a swift decompressive laparotomy with the detection of retroperitoneal hematoma with subsequent hemodynamic stabilization.